Rural Democracy and Communitarian Clientelism: A Study in Sik, Kedah, Post-State Elections 2023 - Baharom, Hazman M.B. (Kajian Malaysia, 2026)
This article challenges the assumption that once democracy is established in a state, it adheres to liberal democratic mechanisms. In contentious rural areas of Malaysia, such as Sik, unique factors, including communal politics, grassroots education, and community engagement, play a significant role. This study analyses why certain figures, such as Kedah Chief Minister, Dato’ Seri Muhammad Sanusi Md Nor, gain popularity despite insufficient explanation by existing theories. Based on original data from in-depth interviews with local political leaders and participant observation, this article explores the factors influencing voting patterns in Sik and their implications for the wider Kedah region during the 2023 Malaysian State Elections. It applies the political concept of ‘clientelism’ as found is previous research and incorporating a communitarian dimension, leading to the proposition of ‘communitarian clientelism’ to better understand diverse democratic practices.